Molecular Identification and Biotechnological Potential of Cerithidea cingulata-and Lottia scabra Associated Fungi as Extracellular Enzyme Producer and Anti-Vibriosis Agent - Agus Trianto; Ocky Karna Radjasa; Subagiyo Subagiyo; Armeilia Ardiva Isabella; Muhammad Syaifudien Bahry; Hartuti Purnaweni; Rignolda Djamaludin; Aiyen Tjoa; Ian Singleton; Darren Mark Evans; Karen Diele (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Mangroves are complex, unique, and dynamic ecosystems that host organisms that have special physiological adaptations to fluctuations in salinity, temperature, and pH. Gastropods have an important role in the mangrove ecosystem for food cycles and webs by helping to provide nutrients and micro-habitats for microbes.  Micro-fungi isolated from mangrove ecosystems are productive sources of enzymes and bioactive compounds such as antibacterial and antifungal. In this study a explored the enzymatic and anti-vibrio activity of fungi associated with the marine gastropod Cerithidea cingulata and Lottia scabra. collected in three mangrove forests in North Sulawesi, Indonesia.  The fungi associated with the specimens were inoculated on malt extract agar (MEA) using the tapping method. Enzymatic and anti-vibrio assays were conducted applying the plug method. Positive effects of the fungal compounds on Vibrio  were indicated by  clear zones formed around the isolates.  A total of 13 fungal species were isolated from C. cingulata (19MB-C5  and 19MBa-A4) and L. scabra (19MT-07 and 19MT-18).  Most fungal isolates have moderate growth rate. The isolate with highest cellulolytic, proteolytic, and anti-vibriosis activity (Vibrio parahaemolyticus, V. harveyi, V. vulnificus, and V. alginolyticus), derived from C. cingulata 19MB-C5 was closely related to Aspergillus niger, as revealed by molecular analysis using the universal primers ITS1 and ITS4 (similarity value 99%).  A. niger 19MB-C5-3 has potential as a bioremediation and anti-vibrio agent that can be applied in aquaculture.